Banking marketing of deposits accounts on promotional tools / Babelin Bellon - Bellon, Babelin (1996)
As financial institutions grows like mushrooms in rainy day, question of "How many big banks there will be?" is difficult to see. With the intention to be remained there, actions, strategies and decisions of marketing is suggested to be made. This dissertation of "Banking Marketing of Deposits Accounts on Promotional Tools" gives a view on the importance of Savings Account, Current Account and Fixed Deposits to banks. Competitors in the line of banking are not only between banks but also to other financial intermediaries. In order to bring out services and products of the banks, promotion is the answer. Promotion create of awareness, interest, direction and action to be taken by the existing depositors or public. In Malaysia, incentives that used and offered as promotional tools by local banks are in term of interest and products. Selection of tools that used are identified through the importance of the specific accounts or schemes to total deposits.